CHARACTERIZATION AND APPLICATION OF NEW EFFICIENT NANOSORBENT Fe₂O₃ PREPARED BY A MODIFIED LOW-TEMPERATURE UREA METHOD - RADOVIĆ VUČIĆ, Miljana; MITROVIĆ, Jelena; KOSTIĆ, Miloš; VELINOV, Nena; NAJDANOVIĆ, Slobodan; BOJIĆ, Danijela; BOJIĆ, Aleksandar (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In this work, low-cost non-conventional nanostructured Fe2O3 was produced by a modified low-temperature urea method (MLTUM-Fe2O3). Non-magnetic amorphous nanoparticle MLTUM-Fe2O3 with a bouquet like morphology is found to play as an effective sorbent media to remove textile dye Reactive Blue 19 from textile industries dye effluents over a wide range of pH. The nanoparticles were characterized by X-ray powder diffraction analysis (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), FTIR and TGA. The surface area was measured by Brunauer-Emmett-Teller (BET) analysis. SEM image reveals bouquet like morphology with average particle size about 50 nm. The maximum sorption capacity of the sorbent is found to be 271.00 mg g–1 for Reactive Blue 19 and the data fitted with different isotherm models. Study on sorption kinetics shows that sorption of Reactive Blue 19 onto iron oxide follows pseudo-second-order kinetic.